Deep-water calibration of echosounders used for biomass surveys and species identification. (2nd December 2017) - Haris, Kunnath; Kloser, Rudy J; Ryan, Tim E; Malan, Jacques
Abstract: Acoustic quantification of aquatic biomass using echosounders requires accurate calibration. With the advancing applications of deep-water echosounders involving moored, towed, profiling and autonomous instruments, calibration of echosounders at the operating depth is needed to ensure unbiased estimates of biomass and species identification. In this context, the deepwater calibration acoustic facility (DeCAF) was used to examine the depth-dependent variations in on-axis gain (G 0 ) and equivalent two-way beam angle (Ψ ) of three different transducers, operating at 38 (Simrad ES38-DD and MSI-38) and 120 kHz (Simrad ES120-7CD) used for biomass surveys and species identification. The analyses carried out using the sphere calibration method reveal significant variations in calibrated G 0 and Ψ that in combination could result in substantial systemic biases in quantitative biomass estimation and species identification. The depth-dependent G 0 variations derived using the DeCAF system are in accordance with available deep-water calibration results, demonstrating reasonable repeatability of target strength measurements (±0.6 dB) over the calibration deployments. Importantly, Ψ of the transducers was calculated to be consistently lower than the values specified by the manufacturer, and for one transducer would result in 18% change in the estimated biomass. These results highlight the potential for bias if the Ψ of transducer is not independently calculated using the actual survey echosounder.